Blinatumomab for treating pediatric B-lineage acute lymphoblastic leukemia: A retrospective real-world study - Wu, Ying; Li, Yanming; Fan, Jia; Qi, Peijing; Lin, Wei; Yang, Jie; Liu, Huiqing; Wang, Xiaoling; Zheng, Huyong; Wang, Tianyou; Zhang, Ruidong (Frontiers in Pediatrics, 2022)
Objectives: Blinatumomab was shown to be safe and effective for consolidation therapy in B-cell acute lymphoblastic leukemia (B-ALL). This study aimed to investigate the effectiveness and safety of blinatumomab in pediatric B-ALL patients in a real-world setting. Methods: This was a retrospective, observational study that included patients who initiated blinatumomab treatment between October 1, 2020 and June 20, 2022. Patients with B-ALL diagnosis, age below 18 years, and at least one blinatumomab treatment cycle were included. Treatment-related toxicities were assessed. Result: Totally 23 pediatric patients were included in this study, with a median age of 6 years (range, 2 to 11 years). Blinatumomab therapy was applied for MRD-positive (disease ≥0.01%, n=3) or chemotherapy-ineligible (n=20) B-ALL cases. The median follow-up time was 9 months, and all evaluable patients achieved complete molecular remission with undetectable MRD. Four relapsed B-ALL cases proceeded to hematopoietic stem cell transplantation (HSCT) without further bridging therapy, while the others underwent maintenance chemotherapy after blinatumomab treatment. Grade ≥3 febrile neutropenia, white blood cell decrease and seizure were observed in 57%, 48% and 4.3% of patients, respectively. One case discontinued therapy due to neurologic toxicities. Elevated cytokine levels were observed in 4 patients. In all 23 patients, increased T-cell and low B-cell counts (＜10/μL) were detected during blinatumomab therapy. Conclusion: These encouraging results suggest blinatumomab in pediatric B-ALL patients with MRD+ or chemotherapy-related toxicities is effective and safe in the short run, although long-term follow-up is still needed.